Solution NMR of SNAREs, complexin and α-synuclein in association with membrane-mimetics - Liang, Binyong (Prog Nucl Magn Reson Spectrosc, 2018)
SNARE-mediated membrane fusion is a ubiquitous process responsible for intracellular vesicle trafficking, including membrane fusion in exocytosis that leads to hormone and neurotransmitter release. The proteins that facilitate this process are highly dynamic and adopt multiple conformations when they interact with other proteins and lipids as they form highly regulated molecular machines that operate on membranes. Solution NMR is an ideal method to capture high-resolution glimpses of the molecular transformations that take place when these proteins come together and work on membranes. Since solution NMR has limitations on the size of proteins and complexes that can be studied, lipid bilayer model membranes cannot be used in these approaches, so the relevant interactions are typically studied in various types of membrane-mimetics that are tractable by solution NMR methods. In this review we therefore first summarize different membrane-mimetic systems that are commonly used or that show promise for solution NMR studies of membrane-interacting proteins. We then summarize recent NMR studies on two SNARE proteins, syntaxin and synaptobrevin, and two related regulatory proteins, complexin and α-synuclein, and their interactions with membrane lipids. These studies provide a structural and dynamical framework for how these proteins might carry out their functions in the vicinity of lipid membranes. The common theme throughout these studies is that membrane interactions have major influences on the structural dynamics of these proteins that cannot be ignored when attempting to explain their functions in contemporary models of SNARE-mediated membrane fusion.